Desenvolvimento de um software web para acompanhamento do desempenho de alunos em provas de autoescolas - Garcia, Arthur Duarte da Costa (Brasil, 2022)
Currently, to acquire the National Driver's License, Brazilians need to carry out assessments at the State Department of Transit in their state. However, the student will first need to attend the theoretical classes offered by the Driver Training Centers or Driving Schools, and later take the practical tests applied by DETRAN. Considering the difficulty of driving school students in fixing content to achieve approval in assessments, the objective of the present study was to develop a web system that can verify the performance of students in tests in driving schools. For the development of the web system, analyzes and bibliographic studies were carried out for a better understanding of the teaching methodology in the place of application of the tests. After that, the necessary requirements of the work were defined. Through the results obtained, driving schools will be able to have a more detailed monitoring of the performance of their students, being able to create methodologies that aim to improve teaching in their companies.